1975
DOI: 10.1002/asi.4630260206
|View full text |Cite
|
Sign up to set email alerts
|

Abstract readability as a factor in information systems

Abstract: Documents may be accessed by increasingly efficient retrieval of abstracts, but information will not be transferred unless the abstracts are read. It is suggested that the measurement of the readability of abstracts can provide an assessment of one phase of an information system: the system/user interface. Controlled reading levels for abstracts could result in more rapid processing of abstracts and a wider use of the information system. It was hypothesized that the use of readability principles in guidelines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

1976
1976
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 8 publications
3
11
0
1
Order By: Relevance
“…The results of the readability score analyses agree with the previous work of Dronberger and Kowitz [15] and King [21]: abstracts tend to be slightly harder to read than full texts, and more difficult full texts tend to have more difficult abstracts.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results of the readability score analyses agree with the previous work of Dronberger and Kowitz [15] and King [21]: abstracts tend to be slightly harder to read than full texts, and more difficult full texts tend to have more difficult abstracts.…”
Section: Discussionsupporting
confidence: 87%
“…Tibbo [34] compared content of chemical, psychological, and historical abstracts with the ANSI standard, and developed and tested a framework of essential information for history abstracts. With regard to style, Dronberger and Kowitz [15], using the Flesch formula, found ERIC abstracts to be on average slightly harder to read than the original documents: King [21] obtained a similar result using another readability formula on Child Del'elopmelll Abstracts. Subjective difficulty as measured by Morris [28] shows a similar relationship.…”
Section: Introductionmentioning
confidence: 99%
“…There has, however, been some concern about the readability of abstracts. For example, Dronberger and Kowitz (1975), using the Flesch Readability formula, found that many of their sample of 48 abstracts published by the Educational Resources Information Clearinghouse (ERIC) were significantly more difficult to read than were samples of text taken from their related articles. Similarly, King (1976), using cloze-type comprehension tests (which involve filling in missing words), found that 30 abstracts taken from Child Development were significantly more difficult to read than were their corresponding articles.…”
Section: Introductionmentioning
confidence: 99%
“…En este contexto, hemos de señalar las influencias de los estudios sobre el concepto de estrategias lectoras Solé, 1992 y las investigaciones de evaluación de la comprensión lectora (Spiro y Brewer, 1980;Gregg y Steingerg, 1980;Dijk y Kintsch, 1983;Berite y Scardamalia, 1987;Kintsch, 1998;Johnson, 1989;Baumann, 1990;Peronard, 1994, Puente, 2001. Esta línea abrió toda una serie de estudios sobre la legibilidad como factor determinante de la comprensión (Dronberger y Kowitz, 1975;Rosemary, 1976;Mayes, 1978;Urquhart, 1979, etc. ), aplicados después al estudio del resumen documental como uno de los criterios de calidad del mismo (Hartley, 1994(Hartley, , 1996(Hartley, , 1997(Hartley, , 2000a(Hartley, , 2000b.…”
Section: Perspectivas Socio-cognitivas Orientadas Hacia La Actividad unclassified